Analisis Implementasi Praktik Kerja Industri Di Sekolah Menengah Kejuruan Muhammadiyah 7 Gondanglegi - Kalean, Imayati; Syaifuddin, Mohammad (Jurnal Kebijakan dan Pengembangan Pendidikan, 2016)
Abstract: This research aims to describe the implementation of industrial work practices in the 7th Vocational High School Muhammadiyah Gondanglegi which includes procedures for the implementation of Internship, implementation of Internship, and obstacles in the implementation of Internship. This research uses a qualitative method with a descriptive type. The subject of this research is the pre-engineering teacher. Data collection techniques used were interviews and document study. While the data analysis technique uses qualitative data analysis techniques. Test the validity of the data using member checking and triangulation. The results of this study are the procedures for implementing Internship used are DU/DI data collection, the preparatory meeting I, submission of an application to DU/DI, registering participants in the internship with DU/DI, preparatory meeting II, procurement of internship, meetings with student guardians, implementation of internship, monitoring, making the internship report, internship exam, and internship evaluation. The implementation of the internship has been running quite well, but it is necessary to evaluate several things, namely the implementation procedure of Internship, the briefing of Internship, monitoring system, guidance system, the involvement of DU/DI in the implementation of Internship planning, and the involvement of DU/DI in the evaluation of Internship. Barriers to the implementation of Internships are: students 'maturity is lacking, students' character and work ethics are minimal, where an internship is not by the wishes of students, school communication and foundations have not been maximized to realize international Internship.Keywords: Industrial Work Practices, Procedures, ImplementationÂ Abstrak: Penelitian ini bertujuan untuk mendeskripsikan implementasi praktik kerja industri di Sekolah Menengah Kejuruan 7 Muhammadiyah Gondanglegi yang meliputi prosedur implementasi prakerin, implementasi prakerin, dan hambatan dalam implementasi prakerin. Penelitian ini menggunakan metode kualitatif dengan jenis deskriptif. Subjek penelitian ini adalah guru pengampu prakjerin. Teknik pengumpulan data yang digunakan adalah wawancara dan studi dokumen. Sedangkan teknik analisis data menggunakan teknik analisis data kualitatif. Uji keabsahan data menggunakan member checking dan triangulasi. Hasil penelitian ini menunjukkan bahwa prosedur implementasi prakerin yang digunakan yaitu pendataan DU/DI, rapat Persiapan I, pengajuan surat permohonan ke DU/DI, mendata peserta prakerin dengan DU/DI, rapat persiapan II, pembekalan prakerin, rapat bersama wali murid, pelaksanaan prakerin, monitoring, pembuatan laporan prakerin, ujian prakerin, dan evaluasi prakerin. Implementasi prakerin sudah berjalan cukup baik, tetapi perlu dilakukan evaluasi terhadap beberapa hal yaitu prosedur pelaksanaan prakerin, pembekalan prakerin, sistem monitoring, sistem pembinaan, keterlibatan DU/DI dalam perencanaan pelaksanaan prakerin, dan keterlibatan DU/DI dalam evaluasi prakerin. Hambatan implementasi prakerin adalah: kedewasaan berpikir siswa kurang, karakter dan etika kerja siswa minim, tempat prakerin tidak sesuai dengan keinginan siswa, komunikasi sekolah dan yayasan belum maksimal untuk mewujudkan prakerin internasional.Â Kata kunci: Praktik Kerja Industri, Prosedur, Implementasi